Cyclic and Linear Thiopeptides from Soil‐Derived Streptomyces sp. CPCC 203702 with Antiviral and Antibacterial Activities. Issue 12 (4th October 2021) - Zhang, Dewu; Wang, Yujia; Hu, Xinxin; Wang, Xiaoyu; Li, Linzi; Gu, Guowei; Zhang, Bingyuan; Cen, Shan; You, Xuefu; Yu, Liyan
Main observation and conclusion: A new cyclic thiopeptide, berninamycin F (3), three new linear thiopeptides, berninamycins G—I (4—6), and two known berninamycin derivatives, berninamycins C and D (1 and 2) were isolated from Streptomyces sp. CPCC 203702. Their structures were elucidated through HRESIMS and one‐ and two‐dimensional NMR data, and the absolute configurations were assigned using Marfey's method. Compounds 4—6 are the first examples of linear berninamycin analogs. Notably, compound 4 is the first example of linear thiopeptide with a 1‐(oxazol‐2‐yl)ethan‐1‐one group, compound 6 is the first linear thiopeptide derivative with methylated oxoacetate moiety. Compounds 1—6 exhibited excellent anti‐Zika virus activities with IC50 values in the range of 4.4—10.5 μmol/L, which were superior to that of the positive control ribavirin (IC50 = 49.2 μmol/L). Compounds 1 and 3 showed strong anti‐influenza A virus activities with the IC50 values of 15.6 and 3.2 μmol/L, respectively. Compound 1 exhibited good antibacterial activities against methicillin‐resistant Staphylococcus aureus and vancomycin‐resistant Enterococcus spp. pathogens. Abstract : A new cyclic thiopeptide, three new linear thiopeptides, and two known berninamycin derivatives were isolated from Streptomyces sp. CPCC 203702. All compounds exhibited excellent anti‐ZIKV activities, compounds 1 and 3 showed strong anti‐IAV activities, and compound 1 exhibited good antibacterial activities against methicillin‐resistant Staphylococcus aureus and vancomycin‐resistant Enterococcus spp. pathogens.